Analisis Kebutuhan Media Storyline dalam Pembelajaran Sejarah Guna Meningkatkan Berpikir Kronologis Siswa Fase E SMAN 1 Basa Ampek Balai Tapan - Syahri, Rahmanda; Yefterson, Ridho Bayu (Jurnal Kronologi, 2025)
This study analyzes the need for storyline video media in history learning to improve the chronological thinking skills of grade X Phase E students at SMAN 1 Basa Ampek Balai Tapan. The background of this study is the low ability of students to organize historical events sequentially, which is caused by limited variations in learning media. Teachers still predominantly use lectures and written texts. The approach used is descriptive qualitative, with data collection through observation, interviews, and pretests to measure students' chronological thinking skills. The results show that this ability is still low, with only around 23%–36% of students able to answer chronology-based questions correctly. The needs analysis indicates the importance of developing storyline video media that presents visualizations of events in a sequential, interactive, and engaging manner. This media is considered effective in helping students understand the relationship between time and cause and effect in history. Support for school facilities and smartphone ownership by students also strengthen the potential for its application. Therefore, the development of storyline video media for the material on the Patterns of Life in the Prehistoric Period is considered strategic in improving chronological thinking skills while supporting the achievement of history learning according to the Independent Curriculum. ABSTRAK Penelitian ini menganalisis kebutuhan media video storyline dalam pembelajaran sejarah untuk meningkatkan keterampilan berpikir kronologis siswa kelas X Fase E di SMAN 1 Basa Ampek Balai Tapan. Latar belakang penelitian ini adalah rendahnya kemampuan siswa dalam menyusun peristiwa sejarah secara runtut, yang disebabkan oleh keterbatasan variasi media pembelajaran. Guru masih dominan menggunakan metode ceramah dan teks tertulis. Pendekatan yang digunakan adalah deskriptif kualitatif, dengan pengumpulan data melalui observasi, wawancara, serta pretest untuk mengukur kemampuan berpikir kronologis siswa. Hasil menunjukkan bahwa kemampuan tersebut masih rendah, dengan hanya sekitar 23%–36% siswa yang mampu menjawab soal berbasis kronologi dengan benar. Analisis kebutuhan menunjukkan pentingnya pengembangan media video storyline yang menyajikan visualisasi peristiwa secara runtut, interaktif, dan menarik. Media ini dinilai efektif dalam membantu siswa memahami hubungan waktu dan sebab-akibat dalam sejarah. Dukungan sarana sekolah dan kepemilikan smartphone oleh siswa turut memperkuat potensi penerapannya. Oleh karena itu, pengembangan media video storyline pada materi Corak Kehidupan Masa Praaksara dianggap strategis dalam meningkatkan keterampilan berpikir kronologis sekaligus mendukung capaian pembelajaran sejarah sesuai Kurikulum Merdeka.